ЗАРОЖДЕНИЕ И РОСТ ИНДИВИДОВ В ДРУЗАХ РАСЩЕПЛЕННОГО КВАРЦА (ВОСТОЧНАЯ ЯКУТИЯ) - Суставов О.А. (My University, 2005)
The study was carried out for druses of the Iя type (as thick as 0.2-4 mm) - with zones of geometric selection in the basis, with columnar quartz individuals elongated by с axis, overgrowing as quartz-free, so the quartz-bearing (arkosic-graywacke sandstones) and the mere quartz (monocrystal and small-grained) matrix. It is shown that orientation of the с axis in quartz individuals of those druses depends as on geometric selection in their growth, so on abundance of nuclcation of the favorably directed individuals. On the quartz-free and mono-crystal quartz matrix, equally, the regularly directed individuals are often forming bunches which appearance is connected with radial splitting caused by tangential off-growing of basis's of columnar individuals along the substratum surface. While the regenerating nuclcation of individuals on quartz grains of matrix, the predominant nucleation of the favorably directed individuals appears, in one or another degree, as a «selective» regeneration of mainly the regularly oriented matrix grains. During the growth there was remarked a gradual curve of c-axis of individuals to direction favorable for growing. Dimensions of columnar individuals arc changing according to sizes of adversely oriented grains in the geometric selection zone.
Keywords: 549.514.51:548.5